Description of Loraxichthys lexa, new genus and species (Siluriformes: Loricariidae) from the Río Huallaga Basin, central Peru, with notes on the morphology of the enigmatic Lipopterichthys carrioni Norman, 1935 - Salcedo, Norma J. (Zootaxa, 2013)
A new genus and species of armored catfish, Loraxichthys lexa, collected in 1955 by the Catherwood Foundation Peruvi-an-Amazon Expedition from the vicinity of Tingo María, Huánuco, is described herein. Loraxichthys is diagnosed by two uniquely derived characters: two to four robust evertible posterior cheek odontodes with hooked tips, longer than odon-todes anterior to them but no more than twice their length; and skin folds on dorsal border along first pelvic-fin ray cren-ulated in mature males. Loraxichthys lexa, new species, is only known from clear water tributaries of the Río Huallaga in the vicinity of Tingo María. Additionally, notes on the morphology of the enigmatic species Lipopterichthys carrioni are included, and an artificial key for the genera Chaetostoma, Cordylancistrus, Dolichancistrus, Leptoancistrus, Lipopter-ichthys, and Loraxichthys is provided.